PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PLOTAGON KELAS VI PADA TEMA 1 SUBTEMA 3 PEMBELAJARAN 1 - Talitha Lutfiyah Kurtubi; Surti Kurniasih; Rukmini Handayani (STKIP Subang, 2024)
This research aims to determine the development of Plotagon-Based Learning Media in the Let's Save Animals and Plants sub-theme in class VI SDN Bantarjati 5 Bogor, as well as determine the suitability of learning media in the learning process. The method used in this research is the ADDIE method (Analysis, Design, Development, Implementation and Evaluation). In this research, validation tests were carried out on media experts, material experts and language experts to develop and perfect Plotagon-based learning media products for students. The data results from media expert validation were 100%, which means it is very feasible to implement, the results from material experts were 86%, which was stated to be very feasible to implement, and the results from language experts were 100%, which means it was very feasible to implement. And based on a limited trial conducted with class VI students, 28 students obtained a score suitable for use of 73.8%, which means that Plotagon-based learning media is suitable for use in the learning process. Keywords: Learning Media, Plotagon.